ANALISIS FAKTOR PENENTU LABA DALAM PERHITUNGAN HARGA POKOK PENJUALAN DI RESTORAN KEMBANG GOELA, PT NUSANTARA BOGA ABADI, JAKARTA SELATAN. - Oktaviani, Riri; Krisanti, Imelda; Gustiyanti, Ferra; Sukardi, Sukardi; Herawati, Tuti; Saksana, Joned C; Hidayatullah, Syarif (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2023)
This research aims to analyze the implementation and acquisition of sales and cost of goods sold on food menus at PT Nusantara Boga Abadi to calculate net sales profit. This research serves as a benchmark to determine whether the profit margin obtained by the company is optimal. The data used are secondary data in the form of raw material purchases. The method used is descriptive analysis with a quantitative approach. PT Nusantara Boga Abadi operates in the food industry, and the focus of this research is